FinTechs and the Market for Financial Analysis. (11th September 2021) - Grennan, Jillian; Michaely, Roni
Abstract: Hundreds of equity market intelligence financial technology firms (FinTechs) have formed in the last decade. We assemble novel data to describe their capabilities, users, and consequences. Our data suggest that these FinTechs i) aggregate many data sources, including nontraditional ones (e.g., Twitter, blogs), and synthesize such data using artificial intelligence to make investment recommendations, and ii) change Internet users' information discovery by serving as substitutes for traditional information providers. We evaluate some nontraditional data and find evidence suggesting that such data contain valuable information or "crowd wisdom" that links to informational efficiency. Overall, our findings are consistent with this innovation benefiting investors and markets.